The role of Smn on motorneuronmuscle unit function and on mouse embryonic development - Shafey, Dina (University of Ottawa (Canada), 2008)
Spinal muscular atrophy (SMA) is a devastating childhood neurodegenerative disorder characterized by the degeneration of the alpha-motor neurons in the spinal cord. The loss of these neurons causes proximal, symmetrical limb and trunk muscle weakness that progresses to paralysis and ultimately to death. The disease causing protein in SMA is called survival motor neuron (SMN). SMA is a disease with ranging severity. Disease severity is inversely related to the amount of SMN a patient produces. Thus SMA is a dose-dependent disease. To gain a better understanding of the pathogenesis of SMA and this dose-dependent effect, we have used short interference RNA (siRNA) to selectively reduce SMN expression in cell culture and transgenic mice. Knockdown of SMN protein levels affects properties of cells in culture and mice during embryonic development. We have observed decreased number of nuclear gems (gemini of coiled bodies), reduced proliferation with no increase in cell death, defects in myoblast fusion, and malformed myotubes in SMN depleted C2C12 cells. In parallel, using shRNA vectors, we have developed knockdown mice. These intermediate SMA models, along with existing severe and mild SMA models, were used to assess neuronal development. We investigated the morphology and differentiation of neurosphere-derived neural stem cells (NSCs) generated from the brains of Smn+/- (mild) and Smn -/-;SMN2 (severe) SMA mice. Neurospheres from the severe mice produced NSCs with increased proliferation during growth and differentiation. These cells produced fewer TuJ1-positive neuronal cells, which displayed morphological alterations and had fewer and shorter neurites. In embryos from the severe model, but not the mild model, we observed a significantly altered morphology of cranial nerves IX and X, which appeared to be partially fused. Lastly, to better understand why Smn depletion preferentially affects neurons and muscle, we have used Tandem Affinity Purification to identify Smn complexes from muscle-like and neuronal-like cells. We have identified cell-specific and stage-specific Smn-interacting proteins, which will help us to better understand the diverse functions of Smn. Altogether, our studies have helped identify the possibility of specific roles for SMN in different cell types; the function of these roles is dependent on the dosage of SMN; and this dosage requirement leads to roles for SMN during development and maintenance of neurons and muscle.
Keywords: Biology, Neuroscience.; Biology, Cell.